Domain General Sequence Operations Contribute to Pre-SMA Involvement in Visuo-spatial Processing - Leek, E. Charles; Yuen, Kenneth S. L; Johnston, Stephen J. (Frontiers in Human Neuroscience, 2016)
This study used 3T MRI to elucidate the functional role of supplementary motor area (SMA) in relation to visuo-spatial processing. A localizer task contrasting sequential number subtraction and repetitive button pressing was used to functionally delineate non-motor sequence processing in pre-SMA, and activity in SMA-proper associated with motor sequencing. Patterns of BOLD responses in these regions were then contrasted to those from two tasks of visuo-spatial processing. In one task participants performed mental rotation in which recognition memory judgments were made to previously memorized 2D novel patterns across image-plane rotations. The other task involved abstract grid navigation in which observers computed a series of imagined location shifts in response to directional (arrow) cues around a mental grid. The results showed overlapping activation in pre-SMA for sequential subtraction and both visuo-spatial tasks. These results suggest that visuo-spatial processing is supported by non-motor sequence operations that involve pre-SMA. More broadly, these data further highlight the functional heterogeneity of pre-SMA, and show that its role extends to processes beyond the planning and online control of movement.